1999
DOI: 10.1034/j.1399-0004.1999.550606.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 11q13 and atopic asthma

Abstract: Asthma is a complex syndrome in which bronchial inflammation and smooth muscle hyperactivity lead to labile airflow obstruction. The commonest form of asthma is that due to atopy, which is an immune disorder where production of IgE to inhaled antigens leads to bronchial mucosal inflammation. The ultimate origins of asthma are interactive environmental and genetic factors. The genetics is acknowledged to be heterogeneous, and one chromosomal region of interest and controversy has been 11q13. To clarify the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 53 publications
3
43
0
Order By: Relevance
“…This fact makes it more reliable that the association found reflects a common biological mechanism since there are more alleles transmitted (73) and non-transmitted (40) with the disease phenotype. Our results support those obtained earlier (Adra et al 1999;Collee et al 1993;Cox et al 1998;Folster-Holst et al 1998;Shirakawa et al 1994Shirakawa et al , 1996van Herwerden et al 1995) indicating that the locus on 11q13 contributes to the development of atopic diseases. Association in non-inbred populations is usually only seen over small distances.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…This fact makes it more reliable that the association found reflects a common biological mechanism since there are more alleles transmitted (73) and non-transmitted (40) with the disease phenotype. Our results support those obtained earlier (Adra et al 1999;Collee et al 1993;Cox et al 1998;Folster-Holst et al 1998;Shirakawa et al 1994Shirakawa et al , 1996van Herwerden et al 1995) indicating that the locus on 11q13 contributes to the development of atopic diseases. Association in non-inbred populations is usually only seen over small distances.…”
Section: Discussionsupporting
confidence: 96%
“…Chromosome 11q13 was the first region to which a putative atopy gene was localised (Cookson et al 1989) and members of the same group later identified the β-subunit of the high-affinity IgE receptor as a candidate gene for atopic diseases (Sandford et al 1993). Other groups (Adra et al 1999;Collee et al 1993;Cox et al 1998;FolsterHolst et al 1998;Hizawa et al 1998;Shirakawa et al 1994Shirakawa et al , 1996van Herwerden et al 1995) have confirmed genetic linkage to the 11q13 region, whereas other groups have not detected linkage to atopic disease (Amelung et al 1992;Brereton et al 1994;Coleman et al 1993;Deichmann et al 1999;Hizawa et al 1992;Lympany et al 1992;Rich et al 1992). We have found only weak evidence in favour of linkage for 11q13 to raised allergenspecific serum IgE levels.…”
Section: Discussionmentioning
confidence: 98%
“…Because the competitive antagonist MK571 interfered with calcium flux in response to both cys-LTs and to UDP, it is likely that the respective binding sites for the two agonists are in close proximity to one another. The genes encoding the P2Y6 receptor and the P2Y2 receptor, which also binds uridine nucleotides, are closely linked on human chromosome 11q13 (29), a region containing genes linked to the inheritance of asthma (30,31). The respective genes encoding the CysLT1 receptor and the P2Y4 receptor, both of which are expressed by hMCs, are closely linked on human chromosome Xq13-21, another region containing candidate asthma genes (19).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the chromosome 11q some studies have confirmed the linkage of atopy and bronchial hyperresponsiveness to markers on 11q13 (Adra et al 1999;Collée et al 1993;Daniels et al 1996;van Herwerden et al 1995;Mao et al 1997;Shirakawa et al 1994a;Young et al 1992), while others have failed to find the linkage (Amelung et al 1992; Collaborative Study on the Genetics of Asthma 1997; Hizawa et al 1992;Lympany et al 1992;Malerba et al 1999;Ober et al 1998;Rich et al 1992;Wjst et al 1999;Yokouchi et al 2000). Meanwhile, the gene for the β-chain of the high-affinity receptor for IgE (FcεRIβ) has been identified as a candidate gene for this linkage between atopy and 11q13 (Sandford et al 1993), and two coding variants in exon 6 of FcεRIβ, Ile181Leu/Ile183Val and Ile181Leu, are reported to be associated with atopy in British subjects (Shirakawa et al 1994b).…”
Section: Introductionmentioning
confidence: 93%